Implementation of The Balanced Scorecard In Improving The Performance of University Business Incubator (Case Study : Inkubator Bisnis Teknologi Universitas Andalas) - Prima Fithri; Alizar Hasan; Fandy Triawan; Ikhwan Arief; Asmuliardi Muluk (Management Institute Faculty of Economics Universitas Andalas, 2023)
Andalas University has a business incubator unit called the Technology Business Incubator (InBisTek) Andalas University. This study aims to formulate Key Performance Indicators and measure the performance of Inbistek Andalas University in assisting tenants. Performance measurement is carried out using the Balanced Scorecard method which consists of: on four perspectives namely internal business process perspective, growth and learning perspective, financial perspective, and tenants perspective. Performance measurement is carried out using data obtained from direct observation, questionnaires, and interview directly with the Andalas University Inbistek. KPI formulation is followed by a validation step,so that 31 selected KPIs were obtained. Furthermore, the selected KPIs are continued with weighting to determine the level interest in each KPI through a pairwise comparison questionnaire with the Analytical Hierarchy Process method. Then the performance measurement is carried out according to the perspective on the Balanced Scorecard. Obtained results of performance measurement Andalas University Institute of Technology as a whole is 3.4 which is included in the good category. Based on the results performance measurement, there are 5 KPIs with poor performance category, 5 KPIs with fairly good performance category, 12 KPIs withgood performance category, and 9 KPIs with very good performance category.